A new immunohistochemical method to evaluate the development of vestibular compensation after unilateral labyrinthectomy in rats. (3rd June 2019) - Matsuda, Kazunori; Kitahara, Tadashi; Ito, Taeko; Fukushima, Munehisa; Fukuda, Junya; Sato, Go; Kitamura, Yoshiaki; Abe, Koji; Uno, Atsuhiko; Tomita, Koichi; Sakata-Haga, Hiromi; Fukui, Yoshihiro; et al.
Abstract: Background: Unilateral labyrinthectomy (UL) causes the disappearance of ipsilateral medial vestibular nuclear (ipsi-MVe) activity and induces spontaneous nystagmus (SN), which disappears during the initial process of vestibular compensation (VC). Ipsi-MVe-activity restores in the late process of VC. Objective: We evaluated the late process of VC after UL in rats and examined the effects of thioperamide (H3 antagonist) on VC. Materials and methods: MK801 (NMDA antagonist)-induced Fos-like immunoreactive (-LIR) neurons in contra-MVe, which had been suppressed by NMDA-mediated cerebellar inhibition in UL rats was used as an index. Results: The number of MK801-induced Fos-LIR neurons in contra-MVe gradually decreased to the same level as that of sham-operated rats 14 days after UL. Thioperamide moved the disappearance of the MK801-induced Fos-LIR neurons 2 days earlier. The number of MK801-induced Fos-LIR neurons in thioperamide-treated rats was significantly decreased, compared with that of vehicle rats on days 7 and 12 after UL. But, thioperamide did not influence the decline of SN frequency in UL rats. Conclusion: These findings suggested that the number of MK801-induced Fos-LIR neurons in contra-MVe was decreased in concordance with the restoration of ipsi-MVe-activity during the late process of VC after UL and that thioperamide accelerated the late, but not the initial process of VC.